Employee Retention in Chinese SMEs: a case study of a retail pharmacy - Wang, Yeqi (2019)
With the increasing number of small and medium-sized enterprises (SMEs) in China, the problem of how to decrease the turnover rate and remain more employees are becoming a crucial problem. The purpose of this dissertation is to explore the main factors affect employee retention and turnover intention in Chinese SMEs, and analyse some aspects can improve employee retention. Finally， there is a discussion to explore the especial influence of Chinese national culture on employees’ retention and turnover intention in SMEs. To achieve the research objective, this dissertation was designed as a case study in a retail chain pharmacy – TLT pharmacy which with over ten branches in the area. A closed-ended questionnaire was conducted, and the secondary data was collected to accomplish the results of the questionnaire. 118 employees in TLT pharmacy was randomly selected as the respondents for quantitative research. The results of the research demonstrated that the five factors that compensation and rewards; job satisfaction; learning, training and promotion opportunities; relationship with managers and co-workers are positively related to employee retention. It is also suggested what aspects the company need to improve to retain employees. In the end, this research demonstrated that Chinese national culture influenced Chinese SMEs as an important and special factor.